NILAI-NILAI ETIS AGAMA DAN BUDAYA DALAM PRAKTIK PEKERJA SOSIAL - Japarudin Japarudin (JURNAL ILMIAH SYI'AR, 2015)
Although much has been written about the work of social workers, but the practiceof social workers in Indonesia still leaves an empty space to be studied, betweeenis the issue of ethical values. As a profession that was not born in Indonesia, a social worker in praktikya in Indonesia can be exposed to the values and ethical issues, including religious and ethical values and culture. In the social work profession will face two dilemmas and ethical values: (1) the values and ethics that exist in society as a client, (2) values and ethics in social work profession itself. Both can affect the social workers make decisions in the professional practice of social workers.